Perkembangan Digitalisasi Layanan Bumdes sebagai Upaya Modernisasi Perekonomian di Era 5.0 - Afifah, Pipit; Khomsiyati, Siti; Wahid, Moh. Abdurrahman; Fatimah, Siti (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
In order to enhance information technology competency, including in the village economic sector, cooperation between the academic and industrial sectors is required by the digital age and Industrial Revolution 4.0. As is the situation in Teluk Dalem Village, many Village-Owned Enterprises (BUMDes) are still falling behind in their embrace of technology despite the prospects for economic digitization. Efficiency, accountability, and local economic growth are hampered by the BUMDes' continued reliance on manual procedures for recordkeeping, promotion, and services in this hamlet. This program's objective is to enhance BUMDes managers' capabilities by providing them with relevant and organized training on service digitization. Observation, the creation of training materials, interactive training, and the creation and deployment of digital technologies tailored to local requirements were all components of the descriptive qualitative, participatory approach. According to the program's findings, BUMDes managers' knowledge and proficiency with digital tools, including management software, social media digital marketing, and a Google Sheets-based transaction tracking system, have significantly increased. The initiative was successful in boosting service efficiency and transparency while also boosting managers' confidence to keep coming up with new ideas. This initiative demonstrates that digitization is a comprehensive transformation approach in village economic management that goes beyond a technical fix to usher in the inclusive and sustainable Society 5.0 era.